Factors influencing willingness to reduce meat consumption among students in Universiti Putra Malaysia - Kamal, Nur Aisyah; Leby, Jasmine Lau (Human Resource Management Academic Research Society, 2023)
Meat is one of the most consumed and nutritious foods, but excessive consumption is often associated with negative effects on the environment and human health. Based on the Theory of Reasoned Action (TRA), this study aims to understand the relationship between environmental attitude, health attitude, subjective norms and willingness to reduce meat consumption as well as the factors that influence willingness to reduce meat consumption. A total of 202 students of Universiti Putra Malaysia were involved in this study where they were selected using simple random sampling. Data were collected through a set of self-administered questionnaires. The results of the study show that environmental attitudes (r=0.528, p < 0.001), health attitudes (r= 0.595, p < 0.001) and subjective norm (r= 0.455, p < 0.001) have a significant relationship with willingness to reduce meat consumption. Regression results showed that all three determinant variables explain 41.2% of the variability of willingness to reduce meat consumption. Health attitude had the highest beta (?) value of 0.526 (p < 0.001) followed by environmental attitude and subjective norm with beta values of 0.200 (p < 0.001) and 0.086 (p < 0.001), respectively. Therefore, to reduce meat consumption, it is important to use target intervention and communication messages as well as celebrities’ endorsement and social influence.